Improving Students’ Writing Abilyty In Narrative Text Through Short Animated Stories At Grade VIIID OF SMPN 1 Uepai - Iin wahyudi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research was aimed to improve the writing ability through Short Animated Stories at grade VIIID of SMPN 1 Uepai, in the academic year of 2023/2024. This particular research was categorized as action research. The actions were implemented in two cycles based on the class schedule. This research involved the 25 students of class VIIID of SMPN 1 Uepai in the academic year of 2023/2024 and the English teacher as the research collaborator. The data of the study were in the forms of qualitative and quantitative data. The qualitative data were obtained by observing the teaching and learning process of writing, interviewing the students of class VIIID and the English teacher, holding a discussion with the English teacher and taking figures. Meanwhile, the quantitative data were acquired through the pre-test, the progress test, and the post test. The research findings showed that the use of Short Animated Stories combined with the use of some supporting activities and classroom was proven to be effective to improve the students’ writing ability. It could get students’ attention and increased their learning motivation. It can help the students understand the story better as the picture that can help imagining the real situation in the story. In the result of pre-test, the students’ score was 54.32 with the percentage was 16%. In the cycle I, the students’ score was 64.88 with the percentage was 44%, it means that it do not get standard indicator of successfulness. Then the researcher continues the research at the cycle II, the students’ score was 70.44 with the percentage was 72%, it means that they get standard indicator of successfulness. The distance of percent between cycle I and cycle II was 28%. On the next test on post-test, the students’ score was 76.16 with the percentage was 80%. Based on the score of obtained students who analyzed by using qualitative and quantitative showed the score was very significant, thus short animated stories fit in this learning and can improve students’ writing ability.